KERAGAMAN GEN CALPASTATIN, CALPAIN 3 DAN MYOSTATIN PADA DOMBA DI UP3 JONGGOL - Cece Sumantri; . Jakaria; Mohamad Yamin; Henny Nuraini; Bramada Winiar Putra; Eryk Andreas (Jurnal Ilmu Pertanian Indonesia, 2012)
The aim of this study was to identify the genetic polymorphisms of calpastatin (CAST), calpain 3 (CAPN3) and myostatin (MSTN) on local sheep at Jonggol Animal Science Teaching and Research Unit (JASTRU). A total number of 294 blood samples were collected from JASTRU. The identification of polymorhism in CAST and CAPN3 genes performed by using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) while MSTN gene by using PCR-SSCP methods. The results showed that CAST|MspI, CAST|NcoI and CAPN3|MaeII loci were polymorphic, whereas The MSTN locus was monomorphic for G (1.0). The frequency of allele M (0.87) on the locus (CAST|MspI) higher than the N allele (0.13). At locus CAST|NcoI, the frequency of allele M (0.96) higher than the N allele (0.04). At the CAPN3|MaeII, allele G (0.85) and allele T (0.15). Locus CAST|NcoI has higher observed heterozygosity (Ho = 0.92) compared to CAPN3|MaeII and CAST|MspI (Ho = 0.74-0.77), however has lower compared to CAPN3|MaeII and CAST|MspI in expected of heterozygosity (He = 0.08 vs 0.23-0.26) and in index fixation (Fis = -0.04 vs 0.03-0.12).